Anatomic Knowledge and Perceptions of the Adequacy of Anatomic Education Among Applicants to Orthopaedic Residency. (May 2017) - Toogood, Paul; Shaw, Jeremy; Nussenbaum, Fernando; Acosta, Anna; Dawson, Jack; Perkins, Christopher; Firoozabadi, Reza; Lee, Nicolas
Abstract : Background: The time dedicated to the study of human anatomy within medical school curriculums has been substantially reduced. The effect of this on the knowledge of incoming orthopaedic trainees is unknown. The current study aimed to evaluate both the subjective perceptions and objective anatomic knowledge of fourth-year medical students applying for orthopaedic residency. Methods: A multicenter prospective study was performed that assessed 224 students during the course of their interview day for an orthopaedic residency. Participants provided demographic data and a subjective assessment of the quality of their anatomic education, and completed either an upper or lower extremity anatomic examination. Mean total scores and subscores for various anatomic regions and concepts were calculated. Results: Students on average rated the adequacy of their anatomic education as 6.5 on a 10-point scale. Similarly, they rated the level of importance their medical school placed on anatomic education as 6.2 on a 10-point scale. Almost 90% rated the time dedicated to anatomy as good or fair. Of six possible methods for learning anatomy, dissection was rated the highest. On objective examinations, the mean score for correct answers was 44.2%. This improved to 56.4% when correct and acceptable answers were considered. Regardless of anatomic regions or concepts evaluated, percent correct scores did not reach 50%. There were no significant correlations between performance on the anatomic examinations and either prior academic performance measures or the student's subjective assessment of their anatomic education. Conclusions: Current students applying into orthopaedic residency do not appear to be adequately prepared with the prerequisite anatomic knowledge. These deficits must be explicitly addressed during residency training to produce competent, safe orthopaedic surgeons.